A Masterpiece in the Closet: Brass ewer in the Zanjan Archaeological Museum - NOURALLAHI, Ali (Historia i Świat, 2021)
Many large and small museums in the provinces of Iran exhibit objects, containers, and display items that are not well known and are often on loan from other museums. These objects of cultural value have been introduced to these collections at different times and no serious, even elementary research and study has been carried out on them. By introducing this type of objects some of the ideas presented so far may be reviewed and corrected. In this article I have tried to point out how to obtain this design and to describe it accurately and to describe the carved inscriptions on it, then how to make it and its motifs and how these decorations relate to its possible function as well as their possible origin. The author also draws attention to the catastrophic lack of evidence and events that have taken place in recent years in the Middle East and Iran’s western neighbors. In the end, I have briefly summarized various points mentioned above.